PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI PEMBELAJARAN POE (PREDICT OBSERVE EXPLAIN) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUANBERPIKIR KRITIS SISWA DI MAN 1 MATARAM TAHUN PELAJARAN 2012/2013 - Prayogi, Saiful; Hidayat, Samsun; Wulandara, Auliya (Lensa : Jurnal Kependidikan Fisika, 2013)
This study aims to improve learning outcomes and critical thinking skills of students MAN 1 Mataram Academic Year 2012/2013 through the application of cooperative learning model and strategy learning POE (Predict Observe Explain). The type of research used is classroom action research (PTK). This study was conducted in two cycles. Each cycle consists of planning, execution, observation, and reflection. Data on cognitive learning outcomes was obtained from PG tests and critical thinking through LKS. The subjects of the study are students of class X-1 that is 35 people. The results showed that, there is an increase in learning outcomes and students' critical thinking skills after the application of learning models. In the first cycle of classical completeness of cognitive learning results of 48.39%, the second cycle increased to 87.88%. The students' critical thinking ability in the first cycle was 67.28, and the Ikedua cycle increased to 74.62 with critical criteria. It can be concluded that cooperative learning model with POE (Predict Observe Explain) learning strategy has improved yield learning and critical thinking skills of students.